Fairytail. 29, Pawns vs. grandmaster - Mashima, Hiro, 1977- (Kodansha Comics, 2013)
"Fairy Tail's remaining wizards stand against Hades, a former master of the guild who has already defeated his successor, Makarov!"--Back cover.